Migration and career attainment of power couples: the roles of city size and human capital composition. (15th March 2018) - Simon, Curtis J
Abstract: Costa and Kahn (2000, The Quarterly Journal of Economics, 115: 1287–1315) documented that power couples tended to be located in large cities, postulating a need to solve a co-location problem peculiar to dual-career, highly educated spouses. Using data from the 2008 to 2014 American Community Surveys, I find that young full-power couples are more likely to move to larger, better-educated cities relative to couples in which just the husband has a college degree and wife-only power couples more likely than couples in which neither spouse has a college degree. I also present new evidence that larger, better-educated cities offer superior joint husband-and-wife career outcomes as measured by occupational attainment for wives and husbands with college degrees.